A language for trust modelling - Muller, T; Zhang, J; Liu, Y (Springer, 2016)
The computational trust paradigm supposes that it is possible to quantify trust relations that occur within some software systems. The paradigm covers a variety of trust systems, such as trust management systems, reputation systems and trust-based security systems. Different trust systems have different assumptions, and various trust models have been developed on top of these assumptions Typically, trust models are incomparable, or even mutually unintelligible; as a result their evaluation may be circular or biased.We propose a unified language to express the trust models and trust systems. Within the language, all trust models are comparable, and the problem of circularity or bias is mitigated. Moreover, given a complete set of assumptions in the language, a unique trust model is defined.